Constructing Authenticity in Sponsored TIKTOK Skincare Content: A Speech Act Analysis of Indonesian Influencer Discourse - Ahmad Fadli Harahap; Ronika Apriyanti Manik; Ghustiva Liani (Linguistic, English Education and Art (LEEA) Journal, 2026)
This study investigated how Indonesian TikTok skincare influencers constructed authenticity through speech acts in sponsored skincare content. The study was conducted because influencer authenticity has become increasingly important in digital marketing, particularly in social media environments where audiences are more aware of commercial intentions. This research aimed to analyze how speech acts functioned not only as persuasive strategies but also as linguistic resources for constructing expertise, connectedness, integrity, transparency, and originality in influencer discourse. The study employed a qualitative discourse-analytic approach by combining Speech Act Theory and authenticity theory. The data consisted of 40 sponsored skincare video transcripts uploaded by Indonesian TikTok influencers between January and December 2025. The data were collected through non-participant digital observation and analyzed using thematic discourse analysis and pragmatic analysis. The findings showed that assertive speech acts were the most dominant category, followed by expressive, directive, and commissive speech acts, while declarative speech acts were absent from the dataset. Assertive speech acts primarily constructed epistemic authority and expertise through product claims, ingredient explanations, and experiential evaluations. Expressive speech acts contributed to affective authenticity through emotional reactions, praise, humour, and gratitude expressions. Directive speech acts fostered relational engagement through conversational recommendations and instructional guidance, whereas commissive speech acts supported projected authenticity by signalling consistency and future commitment. The study concluded that authenticity in TikTok skincare discourse was not an inherent personal quality but a multidimensional communicative performance continuously negotiated through language, interaction, and platform culture. Keywords: Authenticity Construction, Digital Communication, Skincare Discourse, Speech Acts, TikTok influencers